Preliminary investigation on multi-walled carbon nanotubes filled epoxy composite as electrically conductive adhesive - Muhamad Muaz Nasaruddin, Muhamad Muaz Nasaruddin; Sheikh Md Fadzullah, Siti Hajar; Omar, Ghazali (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
Carbon nanotubes filled epoxy resin is one type of electrically conductive adhesives (ECAs) that is used as interconnect materials in electronic application. Carbon based conductive adhesive usually have lower electrical performance in term of conductivity, compared to silver, which is the most popular filler in metal-filled ECA. The carbon based ECA is however better than silver filled ECA in terms of bonding integrity. The objective of this study is to improve electrical properties of the composite adhesive in terms of sheet resistance without compromising its bonding strength by using different size of multi-walled carbon nanotubes (MWCNTs). The aspect ratio of the two types of MWCNT fillers are of 55.5 and 1666.5, for the large diameter and small diameter, respectively. The filler loading for both MWCNTs varies from 5 wt.% to 12.7 wt.%. From the preliminary study, it has been observed that ECAs of higher MWCNTs’ aspect ratio has better sheet resistance; 4.42kΩ/□ compared to 44.86 kΩ/□ at 10 wt.%. Such observation is supported by morphological analysis of the ECA showing distribution of the MWCNT in the ECA with different diameter size. Further investigation will consider the effect of different aspect ratio of the MWCNT on the mechanical properties of the ECA material, focusing on the interlayer properties of such materials.